Adrenaline rush: Unsuspicious dispensing error causing life threatening wrong drug infusion during living donor liver transplantation - Amer Majeed; Yazan Chaiah; Abdelrahman Hammad; Salma Alkhani; Mohammed Abduhu Amer; Dieter Clemens Broering (Saudi Journal of Anaesthesia, 2025)
Medication errors carry the potential for serious patient harm and even death. Prescription and medication administration errors are common, while the incidence of dispensing errors is less consistent due to difficulties in detection and under-reporting. This case report describes an incident in which a busy pharmacy in a quaternary care hospital dispensed a norepinephrine infusion that actually contained epinephrine. The error became apparent only after the patient, undergoing living donor liver transplantation surgery, developed unexpected, dramatic, and potentially fatal instability, which worsened with progressively higher doses of norepinephrine. The differentials of the presentation were sequentially excluded, leading to the realisation that the contents of the dispensed medicine might have been inaccurate. When a freshly prepared infusion of norepinephrine replaced the pharmacy-supplied bag, the adverse parameters reversed, and the patient stabilised. This case underscores the importance of maintaining a high index of suspicion for medication dispensing errors, as doing so helped identify the cause and ultimately saved the patient’s life.